Ethnic Violence, Local Security and Return Migration: Enclave communities in Kosovo. (14th September 2017) - Joireman, Sandra F.
Abstract: Forced migration has become commonplace in the international political landscape. In 2015, 60 million people were displaced by violence, more than ever before recorded (UNHCR, 2015). While we know that violence leads to displacement, we know little about return migration after conflict – who comes back and where they settle. This article seeks to engage and supplement the literature on return migration after conflict, advocating for a broader understanding of the security choices made by displaced people. Emphasized here is the importance of a local understanding of safety and the role played by enclave communities in providing a secure context in which people can enjoy the society of their co‐ethnics.